2019
DOI: 10.4103/ijt.ijt_74_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of 308-nm monochromatic excimer lamp in the treatment of resistant alopecia areata

Abstract: Context:Treatment of resistant alopecia areata (AA) can be very challenging and include many options with variable efficacy and safety profiles. The 308-nm excimer lamp has been claimed to offer an effective alternative without significant risks, though there exists a lack of guidelines in this setting.Aims:This study aimed to evaluate the efficacy and safety of the 308-nm excimer lamp in treating resistant AA in Iraqi patients.Settings and Design:A prospective interventional study.Subjects and Methods:Eightee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Excimer phototherapy has been used successfully for treating multiple AA and a few cases of AT, for its high-dose monochromatic UV radiation that can trigger apoptosis and induce immunological suppression [11,12,13] . The present study relied on combining intramuscular triamcinolone acetonide with excimer phototherapy to obtain a greater synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Excimer phototherapy has been used successfully for treating multiple AA and a few cases of AT, for its high-dose monochromatic UV radiation that can trigger apoptosis and induce immunological suppression [11,12,13] . The present study relied on combining intramuscular triamcinolone acetonide with excimer phototherapy to obtain a greater synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up continued for 6 months after treatment to assess the level of recurrence. The results significantly affected resistant cases of multiple AA with considerable safety and tolerability (Figure 1) [17].…”
Section: Evidence-based Studiesmentioning
confidence: 99%
“…In 2001, Baltas et al reported using the excimer laser to treat vitiligo [11]. Several studies have investigated the efficacy of 308 excimer on various dermatological disorders such as atopic eczema, mycoses fungoides, and AA [12][13][14][15][16][17]. All AA (single, multiple, and totalis) were identified and treated in those studies.…”
Section: Historical Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has examined whether low-level light therapy (LLLT) and fractional laser treatments, with or without the addition of topical agents, represent safe and effective alternative treatment options. [10][11][12][13][14][15][16] Since then, several studies have been published on AA treatment using fractional lasers. [17][18][19][20][21][22][23][24][25] In this study, we detail our experience in treating patients with recalcitrant AA using fractional laser and LLLT combination therapy and discuss the treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%